Microbiological, Biochemical and Molecular Identification (PCR-RFLP-ITS) of the yeast from sultana grape cultivated in Ain Merane (Wilaya of Chlef, Algeria) - BOUKHENNOUFA, Asmaa; BERBER, Nadia; AISSAOUI, Rachid; Bekada, Ahmed Mohammed Ali (Current Research on Biological Sciences (CRBS). Science Vier., 2016)
Grapes defined as the fruit of the vine, the most cultivated in the world. It is considered a major habitat of many yeast species. This work aims to isolate, purify and characterize species of yeast from the sultana grape (Thompson’s seedless)cultivated in the region of Ain Merane (from Chlef, Algeria). Several tests were performed (microbiological and molecular).Two strains isolated from grape juice obtained by simple grinding.Pichia fermentans and Metschnikowia pulcherrima were confirmed by a genetic approach (ITS-RFLP) using two restriction enzymes (Taq I, and HaeIII), of the region (ITSI, 5.8S rRNA, ITSI) amplified by PCR.
Keywords: Grape, Sultana (Thompson's seedless), Taq I, HaeIII, PCR, ITS rDNA.